2016
DOI: 10.1152/ajpgi.00027.2015
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids promote diethylnitrosamine-induced hepatocellular carcinoma via increased inflammatory signaling

Abstract: Hepatocellular carcinoma (HCC) is the most common hepatic malignancy and the third leading cause of cancer related deaths. Previous studies have implicated bile acids in pathogenesis of HCC, but the mechanisms are not known. We investigated the mechanisms of HCC tumor promotion by bile acids the diethylnitrosamine (DEN)-initiation-cholic acid (CA)-induced tumor promotion protocol in mice. The data show that 0.2% CA treatment resulted in threefold increase in number and size of DEN-induced liver tumors. All tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 35 publications
(57 reference statements)
7
37
0
Order By: Relevance
“…However, recent advances in our understanding of gut microbes, microbial products, and bile acids have provided insight into how imbalances in the gut–liver axis influence the progression from cirrhosis to HCC . Lipopolysaccharide (also known as endotoxin, a potent immunogenic component of certain bacterial cell membranes) can promote hepatocyte damage and transformation by activating immune cells, inducing cytokine secretion, and inducing reactive oxygen species . Furthermore, one of the major roles of the gut microbiome is to metabolize primary bile acids into secondary bile acids to be recirculated as part of the enterohepatic circulation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent advances in our understanding of gut microbes, microbial products, and bile acids have provided insight into how imbalances in the gut–liver axis influence the progression from cirrhosis to HCC . Lipopolysaccharide (also known as endotoxin, a potent immunogenic component of certain bacterial cell membranes) can promote hepatocyte damage and transformation by activating immune cells, inducing cytokine secretion, and inducing reactive oxygen species . Furthermore, one of the major roles of the gut microbiome is to metabolize primary bile acids into secondary bile acids to be recirculated as part of the enterohepatic circulation .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, one of the major roles of the gut microbiome is to metabolize primary bile acids into secondary bile acids to be recirculated as part of the enterohepatic circulation . In cirrhosis, inefficiency in capturing and secreting bile acids results in bile acid accumulation in the liver where they can act as carcinogens . Therefore, the gut microbiota and bile acid analysis can provide the basis for potentially novel biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated deoxycholic acid DCA can cause DNA damage, activation of hepatic stellate cells and the secretion of inflammatory tumor promoting factor. Intrahepatic cholestasis induces excessive fat accumulation, which could cause hepatocyte damage and inflammation, then promotes HCC 24 . Lithocholic acid (LCA) can stimulate the malignant proliferation of colon and breast cancer cells 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids serve as signaling molecules in the liver that regulate lipid and glucose homeostasis [44]. They play an important role in the sustentation of inflammation, and thus the development and promotion of HCC [45,46]. In cancer cells, 95% of fatty acids come from de novo synthesis [47].…”
Section: Discussionmentioning
confidence: 99%